Case Report: Recurrent Deposition in Renal Allografts: A Rare Case of Fibronectin Glomerulopathy Overlooked in Native Kidneys - Wei, Xiaona; Wang, Xiangdong; Zhang, Rui; Liang, Peifen; Liu, Bo; Wang, Lin; Yue, Shuling; Li, Xiaojuan; Chen, Wenfang; Yang, Qiongqiong (Frontiers in Genetics, 2022)
Fibronectin glomerulopathy (FNG) is a rare inherited kidney disease characterized by extensive deposition of fibronectin in the glomeruli, especially in the mesangial and subendothelial regions. The disease progresses slowly and eventually leads to kidney failure in 15–20 years. Here we report an interesting case. The patient presented with proteinuria and was diagnosed as immune complex-mediated glomerulonephritis and lupus nephritis was suspected. This patient progressed to end-stage renal disease after 18 years and received an allogeneic kidney transplant. However, proteinuria recurred 27 months after kidney transplant. The renal biopsy found extensive deposition in glomeruli and the patient was diagnosed as FNG with mass spectrum analysis and confirmed by immunohistochemistry in both native and transplant kidneys. Gene sequencing revealed a missense mutation in the fibronectin 1 (FN1) gene caused the reduced binding to heparin, endothelial cells, and podocytes and impaired stress fiber formation. She had a stable renal function but persistent nephrotic proteinuria after six months of follow-up. Given the persistence of abnormal circulating fibronectin, FNG can recure in renal transplantation. The circulating fibronectin deposit on graft and the renal function progressing after recurrence, and whether renal transplantation is an acceptable treatment for FNG is still debatable.